Program Kawasan Agrowisata Pertanian Talas di Kelurahan Situ Gede Kabupaten Bogor - Riska sukmawati; Edi Santosa (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Taro is one of the leading commodities in Situ Gede village. Situ Gede, an urban village, is one of Bogor City's villages, which has potential as an agrotourism region. The potential of Situ Gede village in support of the agrotourism program has never been documented, so the aim of this activity is to examine the potential of Situ Gede village in supporting agrotourism. The method used in this research is a qualitative method with quantitative instruments. Based on the study results, farmers are the principal livelihood of the Situ Gede area. With the population distribution at the productive age of 25-39 years, the area of land used for agriculture is 46.32 per cent. The sum of taro production in Situ Gede village gives total production in Bogor City of 34%. Keywords: agrotourism, Situ Gede Village, taro